Pengaruh Budaya Kerja dan Penerapan Sasaran Kinerja Pegawai (SKP) Online terhadap Penilaian Prestasi Kerja di Dinas Perdagangan Kota Padang - Giani Hendri Edison Putri; Aldri Frinaldi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2022)
This study aims to identify and explain the influence of work culture and the application of online employee performance targets on job performance assessments at the Padang City Trade Office. Factors that can affect Job Performance are work culture and Online Employee Performance Targets. This research uses the associative quantitative method. The sampling technique used in this study was purposive sampling. The sample in this study were civil servants at the Padang City Trade Office, totaling 78 employees. The data collection tool in this study was a questionnaire using a Likert scale measurement. This study uses multiple linear regression analysis. The results showed that there was a significant influence between work culture on work performance and the result of the R Adjusted Square value of 0.144. Furthermore, in the employee performance target variable on Job Performance Appraisal, there is also a significant influence with the R Adjusted Square value of 0.226 and there is a simultaneous significant influence between Work Culture and Employee Performance Targets on Work Performance seen from the regression test results with an Adjusted R Square value of 0.267. So that it can be concluded that there is a statement or influence partially or simultaneously in this study.